Preparation method of thin film material based on modified transition metal sulfide and application of thin film material in preparation of fire early warning sensor
Through the combination of modified transition metal sulfide nanosheets and cellulose nanofibers, the long response time and irreversibility of traditional fire early warning materials are solved, and the low-cost, fast and circulating fire early warning function is realized, suitable for early warning of fire early warning .
Patent Information
- Application Number
- CN202411464236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing fire warning sensors have a long response time and are difficult to achieve outdoor applications. The irreversibility of graphene oxide-based materials cannot achieve multiple cycle alarms. MXene is costly and the preparation process involves harmful reagents, so it cannot be prepared in batches.
Using ball milling/ultrasound preparation technology to modify transition metal sulfide (TMDs) nanosheets containing hydroxyl groups, combined with cellulose nanofibers with high aspect ratio, to prepare low-cost, mechanically flexible, circulating fire warning intelligence Film material.
It realizes the functions of low-cost, rapid fire warning and solvent resistance. The material has good flame retardancy and structural stability. It can circulate multiple alarms under flame conditions, and is suitable for early fire warning.
Smart Images

Figure CN119286013A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a method for preparing a thin film material based on modified transition metal sulfide and an application of the thin film material in the preparation of a fire warning sensor. Background Art
[0002] Human use of fire has been accompanied by the development of human civilization. However, once fire is out of control, it is easy to cause a fire, posing a serious threat to human life, property and ecological environment. Especially in the context of modern society, with the continuous development and application of a wide variety of flammable polymer materials, the frequency of fire accidents caused by them is also increasing. At present, the fire warning system plays a key role in early fire detection, providing valuable time for personnel evacuation, and also greatly reducing the loss of life and property caused by fire. However, traditional fire warning sensors (such as infrared sensors and smoke sensors) have the disadvantages of long fire response time (>100 s) and difficulty in outdoor application. Therefore, it is particularly important to design and develop new fire warning materials and systems with rapid fire detection functions.
[0003] Mai et al. used the mechanism of resistance transformation caused by thermal reduction of graphene oxide at high temperature, and designed and developed a flame-retardant graphene oxide / silicone resin smart coating by combining with silicone resin. Based on this coating, a new fire warning system was developed (ACS Nano, 2018, 12, 416-424). After that, the work of graphene oxide-based fire warning film / coating was developed and reported. CN109021983A discloses a method for preparing a modified graphene oxide flame-retardant film and its fire warning application. The patent uses the mechanism that ascorbic acid can promote the thermal reduction of graphene oxide. The prepared composite film material realizes the function of rapid alarm at low temperature (below 250°C), but due to the irreversibility of thermal reduction of graphene oxide, the composite film cannot realize multiple cycle alarms. In the face of some complex environments where fires may reignite (such as forest fires), this material system cannot be applied. To this end, CN111254737A discloses a multifunctional MXene coating and its preparation method and application in fire cycle detection and early warning. This technology uses MXene as the main body, combined with water-soluble polymer PVP / PEG and fluorinated silane, to prepare a hydrophobic, flame-retardant and recyclable fire detection multifunctional MXene coating. However, MXene is expensive, the preparation process involves the use of a large number of harmful reagents (hydrofluoric acid), and it cannot be prepared in batches. Therefore, designing a low-cost smart material that can quickly / cyclically warn of fire has important practical application value. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the art, the present invention provides a method for preparing a thin film material based on modified transition metal sulfide and its application in the preparation of a fire warning sensor. The film has the characteristics of low cost, mechanical flexibility, high efficiency flame retardancy, rapid fire warning and solvent resistance, and can be used as a sensor material for early fire warning.
[0005] In the present invention, unlike graphene oxide-based sensor materials that can only provide a single warning (irreversibility of thermal reduction), transition metal sulfides (TMDs) are semiconductor materials, and the resistance of the material itself can change with temperature and is reversible. Therefore, as long as the material changes from room temperature to high temperature, it can change from an insulating state to a conductive state. After connecting the warning system, the function of a cyclic warning of a fire can be realized. In addition, since TMDs itself has excellent thermal stability, the material has good flame retardancy and structural stability under flame conditions, thereby ensuring the reliability of the fire warning performance. However, TMDs raw materials usually exist in the form of multi-layer blocks, which is not only not conducive to the preparation of composite film materials, but also seriously affects the performance of their own physical properties. In addition, since there are no active functional groups on the surface, the dispersibility of TMDs raw materials in solvents is poor, and it is easy to form sedimentation, which is not conducive to the compounding and processing of materials. Therefore, it is particularly important to realize the peeling and surface modification of TMDs sheets. Here, the present invention adopts a ball milling / ultrasonic preparation process, using hydroxyl-containing biomass molecules to achieve the modification of single-layer / few-layer TMDs nanosheets for batch preparation, and endow the TMDs nanosheets with good water dispersibility. In addition, due to the weak interaction between TMDs nanosheets, the network formed by them is generally not ideal in strength, so one-dimensional cellulose nanofibers with a higher aspect ratio are introduced to improve the flexibility and mechanical strength of the two-dimensional TMDs nanosheet network. On the one hand, cellulose nanofibers with a higher aspect ratio themselves have excellent mechanical properties. On the other hand, the hydroxyl groups in its structure can form hydrogen bonds with a large number of oxygen-containing functional groups on the surface of the modified TMDs nanosheets, thereby further improving the mechanical strength of the composite film. The above technologies are the key to preparing TMDs-based smart film materials with low cost, good mechanical properties, and rapid / cyclic warning.
[0006] The method for preparing a thin film material based on modified transition metal sulfide of the present invention comprises the following steps: Step 1: Using hydroxyl-containing biomass molecules as modifiers, block TMDs are modified and exfoliated by ball milling to obtain modified TMDs.
[0007] Step 2: The modified TMDs powder obtained in step 1 is dispersed in deionized water, and the TMDs are further exfoliated under water bath ultrasonic conditions. After centrifugation and washing, a stable modified TMDs nanosheet aqueous dispersion is obtained.
[0008] Step 3: Mix the modified TMDs nanosheet aqueous dispersion and the cellulose nanofiber aqueous dispersion, and obtain a uniform mixed solution after magnetic stirring.
[0009] Step 4: Transfer the obtained mixed solution into a mold and place it in a forced air oven for drying to obtain a composite film.
[0010] In step 1, the hydroxyl-containing biomass molecules are one or more of tannic acid, sodium alginate, and cellulose microcrystals.
[0011] In step 1, the TMDs are one or more of molybdenum disulfide, tungsten disulfide, molybdenum diselenide, and tungsten diselenide. The size of the bulk TMDs is in the range of 10-30 μm.
[0012] In step 1, the ball milling speed is 200-500 rpm, and the ball milling time is in the range of 2-6 h.
[0013] Furthermore, the mass ratio of the hydroxyl-containing biomass molecules to the TMDs is 1:1 to 1:3.
[0014] In step 2, the ultrasonic power is in the range of 50-200 KW, the ultrasonic time is in the range of 10-60 min; the centrifugal speed is in the range of 3000-8000 rpm; the centrifugal time is in the range of 5-20 min; and the number of washing times is in the range of 1-5 times.
[0015] In step 2, the mass ratio of the modified TMDs powder to deionized water is in the range of 1:20 to 1:100.
[0016] In step 3, the diameter of the cellulose nanofibers is in the range of 50-200 nm, and the length is in the range of 5-15 μm.
[0017] Furthermore, the mass ratio of the cellulose nanofibers to the modified TMDs nanosheets is in the range of 1:1 to 1:2.
[0018] In step 3, the magnetic stirring speed is 200-500 rpm, and the stirring time is 1-12 h.
[0019] In step 4, the drying temperature is 40-60°C and the drying time is 6-12 h.
[0020] The invention discloses an application of a thin film material based on modified transition metal sulfide in the preparation of a fire warning sensor.
[0021] The fire warning sensor comprises a low-voltage power supply, a thin film material based on modified transition metal sulfide, and an alarm device, which are connected in series by wires.
[0022] The voltage of the low voltage power supply is 5-25V, preferably 10-20V.
[0023] The thickness of the thin film material based on modified transition metal sulfide is 50-100 μm.
[0024] The beneficial effects of the present invention are embodied in: 1. The preparation method of modified TMDs nanosheets has the advantages of low cost, strong controllability, and batch preparation.
[0025] 2. The preparation process of the film of the present invention is simple and green, and does not involve the use of any harmful reagents.
[0026] 3. The film prepared by the present invention has good mechanical flexibility and strength, and can support weights that are more than 3000 times its own mass.
[0027] 4. The film material of the present invention has excellent flame retardancy, and has both rapid fire response and cyclic early warning functions under flame conditions, and can be used as an ideal fire early warning sensor material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the modified molybdenum disulfide nanosheets in Example 1.
[0029] Figure 2 (a) infrared spectra and (b) thermogravimetric diagrams of tannic acid, massive molybdenum disulfide, and modified molybdenum disulfide in Example 1.
[0030] Figure 3 This is a photograph of the modified molybdenum disulfide nanosheet aqueous dispersion prepared in Example 1 after being stored for two months, demonstrating excellent storage stability and the ability to be prepared in large quantities.
[0031] Figure 4 This is a diagram showing the mechanical flexibility of the composite film paper-1 prepared in Example 1.
[0032] Figure 5 Scanning electron micrographs of the side surface of the composite film paper-1 prepared in Example 1: (a) low magnification; (b) high magnification; showing a multi-layered micro-nano structure similar to mother-of-pearl.
[0033] Figure 6 The mechanical strength of the composite film material prepared in Example 1 is demonstrated. A 16 mg film sample can support a weight that is 3000 times greater than its own weight.
[0034] Figure 7 This is a comparison chart of the composite film paper-1 prepared in Example 1 before and after combustion, showing excellent flame retardancy.
[0035] Figure 8Scanning electron microscope images of (a) the surface and (b) the side of the composite film paper-1 prepared in Example 1 after the combustion test.
[0036] Fig. 9 It is a schematic diagram of the composition of the flame retardant warning sensor system and its fire cycle warning mechanism.
[0037] Fig.10 The test process of the early warning performance of the composite film paper-1 prepared in Example 1 demonstrated the sensitive fire early warning response (less than 3s) and the ability of cyclic early warning.
[0038] Fig.11 This is a resistance change diagram corresponding to 10 flame attack conditions of the composite film paper-1 prepared in Example 1 in the application example.
[0039] Fig.12 Real-time resistance changes of composite films paper-4, paper-5 and paper-6 prepared in Examples 4, 5 and 6. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, the purpose of which is to explain the content of the present invention more specifically and clearly rather than to limit the protection scope of the present invention. Embodiment 1:
[0041] 1. Mix 10g of tannic acid powder and 20g of molybdenum disulfide (size 30 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 500rpm for 6h.
[0042] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:20; the ultrasonic power is 200 KW, and the ultrasonic time is 20 min; then centrifuge and wash 3 times, the centrifugal speed is 8000 rpm, and the centrifugal time is 10 min.
[0043] 3. Mix 20 mL of the modified molybdenum disulfide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 50 nm, length 15 μm), and stir magnetically at room temperature for 12 h at a speed of 500 rpm.
[0044] 4. Next, the uniform mixed solution was transferred to a mold and placed in a forced air oven for drying at 45°C. After drying for 12 h, a composite film paper-1 was obtained.
[0045] Figure 1This is a SEM image of the modified molybdenum disulfide nanosheets in Example 1, showing a few-layer structure with a size of about 500 nm.
[0046] Figure 2 (a) IR spectra and (b) thermogravimetric diagrams of tannic acid, bulk molybdenum disulfide, and modified molybdenum disulfide in Example 1. The results show that tannic acid successfully modified molybdenum disulfide nanosheets.
[0047] Figure 3 This is a photograph of the modified molybdenum disulfide nanosheet aqueous dispersion prepared in Example 1 after being stored for two months, demonstrating excellent storage stability and the ability to be prepared in large quantities.
[0048] Figure 4 This is the mechanical display diagram of the composite film paper-1, showing excellent mechanical flexibility.
[0049] Figure 5 This is a scanning electron microscope image of the side of the composite film paper-1 prepared in Example 1, showing the multi-level micro-nano structure similar to mother-of-pearl.
[0050] Figure 6 The mechanical strength of the composite film material prepared in Example 1 shows that a 16 mg film sample can support a weight that is 3000 times greater than its own weight, demonstrating excellent mechanical strength.
[0051] Figure 7 This is a comparison chart of the composite film paper-1 prepared in Example 1 before and after combustion. After the flame continued to attack for 90 seconds, the film still maintained a complete structure, demonstrating excellent flame retardancy.
[0052] Figure 8 The SEM images of the surface and side of the composite film paper-1 prepared in Example 1 after flame attack show the complete and dense surface structure and the porous side structure.
[0053] Fig.10 The test process of the early warning performance of the composite film paper-1 prepared in Example 1 demonstrated the sensitive fire early warning response (less than 3s) and the ability of cyclic early warning. Embodiment 2:
[0054] 1. Mix 10g of tannic acid powder and 30g of molybdenum disulfide (size 10 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 200rpm for 2h.
[0055] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:100; the ultrasonic power is 50 KW, and the ultrasonic time is 60 min; then centrifuge and wash 5 times, the centrifugal speed is 3000 rpm, and the centrifugal time is 5 min.
[0056] 3. Mix 10 mL of the modified molybdenum disulfide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 200 nm, length 5 μm), and stir magnetically at room temperature for 1 h at a speed of 200 rpm.
[0057] 4. Next, transfer the uniform mixed solution into a mold and place it in a forced air oven for drying at 60°C. After drying for 6 hours, a composite film paper-2 is obtained. Embodiment 3:
[0058] 1. Mix 10g sodium alginate powder and 20g molybdenum disulfide (size 20 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 300rpm for 4h.
[0059] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:50; the ultrasonic power is 100 KW, and the ultrasonic time is 30 min; then centrifuge and wash twice, the centrifugal speed is 6000 rpm, and the centrifugal time is 20 min.
[0060] 3. Mix 15 mL of the modified molybdenum disulfide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 150 nm, length 10 μm), and stir magnetically at room temperature for 6 h at a speed of 300 rpm.
[0061] 4. Next, transfer the uniform mixed solution into a mold and place it in a forced air oven for drying at 50°C. After drying for 8 hours, a composite film paper-3 is obtained. Embodiment 4:
[0062] 1. Mix 15g of tannic acid powder and 20g of tungsten disulfide (size 20 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 200rpm for 6h.
[0063] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:20; the ultrasonic power is 150 KW, and the ultrasonic time is 15 min; then centrifuge and wash 4 times, the centrifugal speed is 5000 rpm, and the centrifugal time is 40 min.
[0064] 3. Mix 10 mL of the modified tungsten disulfide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 50 nm, length 15 μm), and stir magnetically at room temperature for 8 hours at a speed of 500 rpm.
[0065] 4. Next, transfer the uniform mixed solution into a mold and place it in a forced air oven for drying at 40°C. After drying for 12 h, a composite film paper-4 is obtained. Embodiment 5:
[0066] 1. Mix 15g of cellulose microcrystalline powder and 20g of tungsten diselenide (size 20 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 200rpm for 6h.
[0067] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:50; the ultrasonic power is 100 KW, and the ultrasonic time is 15 min; then centrifuge and wash 4 times, the centrifugal speed is 4000 rpm, and the centrifugal time is 30 min.
[0068] 3. Mix 20 mL of the modified tungsten diselenide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 100 nm, length 15 μm), and stir magnetically at room temperature for 6 h at a speed of 300 rpm.
[0069] 4. Next, the uniform mixed solution was transferred to a mold and placed in a forced air oven for drying at 45°C. After drying for 10 h, a composite film paper-5 was obtained. Embodiment 6:
[0070] 1. Mix 10g of tannic acid powder and 20g of molybdenum diselenide (size 30 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 500rpm for 6h.
[0071] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:20; the ultrasonic power is 150 KW, and the ultrasonic time is 30 min; then centrifuge and wash 5 times, the centrifugal speed is 6000 rpm, and the centrifugal time is 20 min.
[0072] 3. Mix 10 mL of the modified molybdenum diselenide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 50 nm, length 10 μm), and stir magnetically at room temperature for 4 h at a speed of 500 rpm.
[0073] 4. Next, transfer the uniform mixed solution into a mold and place it in a forced air oven for drying at 45°C. After drying for 10 h, a composite film paper-6 is obtained. Embodiment 7:
[0074] 1. Mix 10g sodium alginate powder and 20g molybdenum diselenide (size 20 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 300rpm for 4h.
[0075] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:100; the ultrasonic power is 50 KW, and the ultrasonic time is 60 min; then centrifuge and wash 5 times, the centrifugal speed is 8000 rpm, and the centrifugal time is 10 min.
[0076] 3. Mix 15 mL of the modified molybdenum diselenide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 100 nm, length 15 μm), and stir magnetically at room temperature for 6 h at a speed of 300 rpm.
[0077] 4. Next, the uniform mixed solution was transferred to a mold and placed in a forced air oven for drying at 50°C. After drying for 8 h, a composite film paper-7 was obtained. Embodiment 8:
[0078] 1. Mix 20g of cellulose microcrystalline powder and 20g of tungsten disulfide (size 20 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 500rpm for 2h.
[0079] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:50; the ultrasonic power is 100 KW, and the ultrasonic time is 20 min; then centrifuge and wash 3 times, the centrifugal speed is 6000 rpm, and the centrifugal time is 10 min.
[0080] 3. Mix 10 mL of the modified tungsten disulfide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 80 nm, length 10 μm), and stir magnetically at room temperature for 4 h at a speed of 500 rpm.
[0081] 4. Next, the uniform mixed solution was transferred to a mold and placed in a forced air oven for drying at 60°C. After drying for 10 hours, a composite film paper-8 was obtained. Embodiment 9:
[0082] 1. Mix 20g of tannic acid powder and 20g of tungsten diselenide (size 15 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 300rpm for 2h.
[0083] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:30; the ultrasonic power is 150 KW, and the ultrasonic time is 20 min; then centrifuge and wash 4 times, the centrifugal speed is 5000 rpm, and the centrifugal time is 20 min.
[0084] 3. Mix 15 mL of the modified tungsten diselenide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 80 nm, length 10 μm), and stir magnetically at room temperature for 6 h at a speed of 400 rpm.
[0085] 4. Next, the uniform mixed solution was transferred to a mold and placed in a forced air oven for drying at a temperature of 55°C. After drying for 12 hours, a composite film paper-9 was obtained. Embodiment 10:
[0086] 1. Mix 20g of sodium alginate powder and 20g of molybdenum diselenide (size 10 μm) powder, place in a 300ml ball mill, and perform ball milling at a speed of 500rpm for 4h.
[0087] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:50; the ultrasonic power is 100 KW, and the ultrasonic time is 20 min; then centrifuge and wash once, the centrifugal speed is 8000 rpm, and the centrifugal time is 10 min.
[0088] 3. Mix 10 mL of the modified molybdenum diselenide aqueous dispersion with a concentration of 10 mg / mL and 20 mL of cellulose nanofiber aqueous dispersion with a concentration of 10 mg / mL (diameter 100 nm, length 15 μm), and stir magnetically at room temperature for 4 h at a speed of 500 rpm.
[0089] 4. Next, the uniform mixed solution was transferred to a mold and placed in a forced air oven for drying at 45°C. After drying for 12 hours, a composite film paper-10 was obtained. Application Example 1:
[0090] In order to verify that the composite film material prepared by the present invention has sensitive fire response and cyclic warning function, the composite film paper-1 prepared in Example 1 was subjected to a fire warning test, and a low-voltage power supply, a resistor, an alarm light and paper-1 were connected with wires to form a series circuit. Fig.10 At the beginning, the circuit is not conducting, and the alarm light is off; 3s after the flame attacks, the alarm light is triggered; after the flame retreats, the alarm signal disappears immediately, and when the flame attacks again, the circuit conducts again, and the alarm light lights up again. In addition, the applicant also used a resistance meter to monitor the resistance changes of paper-1 under ten flame attack conditions in real time. Fig.11 ,It can be seen that the resistance value of paper-1 decreases rapidly after the flame attack, and the resistance value changes with the flame attack and evacuation, converting between conductor and insulator, thus realizing the function of cyclic fire warning. Fig.12 The real-time resistance changes of the composite films paper-4, paper-5 and paper-6 prepared in Examples 4, 5 and 6 also demonstrated sensitive fire warning response and cyclic warning capabilities.
Claims
1. A method for preparing a thin film material based on modified transition metal sulfide, characterized in that The steps include: Step 1: Using hydroxyl-containing biomass molecules as modifiers, block TMDs are modified and exfoliated by ball milling to obtain modified TMDs; Step 2: dispersing the modified TMDs powder obtained in step 1 in deionized water, further exfoliating the TMDs under water bath ultrasonic conditions, and obtaining a stable aqueous dispersion of modified TMDs nanosheets after centrifugation and washing; Step 3: mixing the modified TMDs nanosheet aqueous dispersion and the cellulose nanofiber aqueous dispersion, and obtaining a uniform mixed solution after magnetic stirring; Step 4: Transfer the obtained mixed solution into a mold and place it in a forced air oven for drying to obtain a composite film.
2. The preparation method according to claim 1, characterized in that: In step 1, the hydroxyl-containing biomass molecules are one or more of tannic acid, sodium alginate, and cellulose microcrystals.
3. The preparation method according to claim 1, characterized in that: In step 1, the TMDs are one or more of molybdenum disulfide, tungsten disulfide, molybdenum diselenide, and tungsten diselenide.
4. The preparation method according to claim 1, 2 or 3, characterized in that: The mass ratio of the hydroxyl-containing biomass molecules to the TMDs is 1:1 to 1:
3.
5. The preparation method according to claim 1, characterized in that: In step 3, the diameter of the cellulose nanofibers is in the range of 50-200 nm, and the length is in the range of 5-15 μm.
6. The preparation method according to claim 1 or 5, characterized in that: The mass ratio of the cellulose nanofibers to the modified TMDs nanosheets is in the range of 1:1 to 1:
2.
7. Use of the thin film material based on modified transition metal sulfide prepared by the preparation method according to any one of claims 1 to 6 in the preparation of fire warning sensors.
8. The use according to claim 7, characterized in that: The fire warning sensor comprises a low-voltage power supply, a thin film material based on modified transition metal sulfide, and an alarm device, which are connected by wires.
9. The use according to claim 8, characterized in that: The voltage of the low voltage power supply is 5-25V.
10. The use according to claim 8, characterized in that: The thickness of the thin film material based on modified transition metal sulfide is 50-100 μm.
Citation Information
Patent Citations
Production method and fire early warning application of flame-retardant modified graphene oxide film
CN109021983A
Solution-phase synthesis of layered transition metal dichalcogenide nanoparticles
CN109790013A
Preparation method of nanocellulose / molybdenum disulfide piezoelectric composite film
CN112646236A
Green, low-cost and efficient preparation method for transition metal disulfide nanosheet
CN112939082A
Reversible composite aerogel for fire early warning and preparation method thereof
JP2024095552A